Pemanfaatan Digital Marketing dan Pendampingan Penyusunan Laporan Keuangan pada UMKM Rumah Peyek di Kelurahan Gunung Bahagia Balikpapan - Adisty Fitria Ramadani; Syaffa’a Amalia Adhwa Islami Pasha; Susanti Susanti; Tri Fatulil Jannah (jurnal ABDIMAS Indonesia, 2023)
Innovation Development is one of the programs that final semester students at STIE Madani must take part in as one of the requirements for completing their education. This program is a form of community service in the economic sector, especially for MSME players, by helping them with mentoring and providing innovation and can help find solutions to the obstacles they face in their business. This activity will last for 3 months from July – October 2023 in Gunung Bahagia Village. The target of the MSMEs that provide assistance is Rumah Peyek, which is one of the home-based MSMEs that produces its own processed peyek products.